Tumoural calcium pyrophosphate dihydrate crystal deposition disease (tophaceous pseudogout) of the hand: A report of two cases including one with a previously unreported associated florid reactive myofibroblastic proliferation - Tan, K.-B. (2012)
10.1080/00313020802436824